Marketing and democracy: similarities and remedies - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Marketing and democracy, two key concepts in the different fields of business and politics, share various traits. Political campaigns, like the landmark victory scored by Barack Obama, were increasingly run in a way that will make most marketing professionals proud. For the better or worse, both concepts have been criticised variously for what they are. Nevertheless, the two can learn and benefit from each other, says Harvard business administration professor John Quelch.